Experimental investigation of oil-water two-phase flow across a large diameter slightly inclined pipe - Samson, John Ndaa (2024)
The production and transportation of oil and water safely and economically across process equipment and pipeline networks have been a major challenge in the process and petroleum industry. In order to properly design the oil-water separator and transportation system, the hydrodynamic behaviour such as the spatial distribution (flow pattern), holdup and pressure drop of the oil–water two-phase flow needs to be well understood. This study aims to experimentally investigate the flow development and interfacial behaviour of oil-water two-phase flow across a large diameter inclined pipe. The pipe geometry used is a 127 mm ID of length 8.4 m with inclination +1o to +5o to the horizontal. The test fluids are tap water (ρ = 998 kg⁄m^3 , μ = 1 mPa.s) and silicone oil (ρ = 916 kg⁄m^3 , μ = 4.7 mPa.s). Three (3) different configurations of fluid inlet devices were used in order to investigate how the phase distributions are affected by the design of the fluid inlet device. The inlet devices are the T-type (first inlet device), Y-type (second inlet device) and Y-type with a separator plate (third inlet device). Four (4) flushed-mounted conductance probes (CP) located at 9.6D (CP1), 19.2D (CP2), 28.8D (CP3) and 56.6D (CP4) from the fluid inlet device (D is the internal diameter of the test pipe) were used to measure the Oil Volume Fraction (OVF) which gives an indication of the region within the pipe cross-section occupied by the oil phase. A double parallel wire probe (DPWP) was fabricated and mounted on the test-pipe to measure the instantaneous height of the water layer which upon analysis will give an indication of the interfacial wave amplitude for a given flow condition. In addition, Phantom V12.1 high-speed camera was used to capture flow images through a viewing box filled with water to avoid image distortion due to the curvature of the pipe.